From the Atlantic to the Pacific: Maruja Mallo in Exile - Shirley Mangini (Studies in 20th & 21st Century Literature, 2006)
Maruja Mallo's life (1902-1995) and art represent one woman's odyssey from the European vanguards to political commitment during the Spanish Republic (1931-1939) and finally to a unique transcendent art form after her wrenching exile from Spain and her residence in Latin America from 1937 to 1965. In her early career she was a leader among the avant-garde painters when few Spanish women were recognized as creative artists. In Latin America, her work diverged radically from European avant-garde trends and from her ideologically oriented subject matter of the 1930s; Mallo not only reflects the impact of her discovery of the Pacific Ocean and her newfound "zest for life," but also clearly defines a new language that celebrates the female body and female sexuality. This essay traces Mallo's personal and artistic journey from Spain to Latin America and back.
Keywords: Maruja Mallo; art theory; art; Europe; Spanish Republic; transcendent; exile; Latin America; avant-garde; painters; ideology; female sexuality; journey